Individualized neuropathic pain therapy based on phenotyping: are we there yet?. Issue 3 (March 2018) - Forstenpointner, Julia; Otto, Jan; Baron, Ralf
Abstract : Abstract: Patients with the same neuropathic pain disorder may have completely different sensory signs and symptoms yet receive the same medicinal treatment. New concepts suggest that patient stratification according to their pain mechanisms, reflected in their sensory phenotype, could be promising to implement an individualized therapy in neuropathic pain. Retrospective classification of patients according to their sensory phenotype showed predictive validity and reliability for treatment response in certain subgroups of patients. Recent prospective studies using stratification based on sensory phenotypes confirm this concept. In this article, we review the recent accomplishments towards an individualized pharmacological treatment of neuropathic pain.